Hamlet - Babra, Neil, 1978-; Shakespeare, William, 1564-1616. (New York : Spark Pub., 2008)
A graphic novel adaptation of William Shakespeare's tragedy in which a Danish prince seeks vengeance for his father's murder after being visited by his ghost.
"SparkNotes."
Adaptation of Hamlet by William Shakespeare.
Booklist
Young Adult
Young Adult
Keywords: Shakespeare, William, -- 1564-1616 -- Adaptations; Shakespeare, William, -- 1564-1616 -- Adaptations; Hamlet (Legendary character) -- Comic books, strips, etc. -- Fiction; Murder -- Comic books, strips, etc. -- Fiction; Princes -- Comic books, strips, etc. -- Fiction; Revenge -- Comic books, strips, etc. -- Fiction; Comic books, strips, etc; Graphic novels; Hamlet (Legendary character) -- Comic books, strips, etc. -- Fiction; Homicide -- Comic books, strips, etc. -- Fiction; Princes -- Comic books, strips, etc. -- Fiction; Revenge -- Comic books, strips, etc. -- Fiction; Graphic novels